Sexual dimorphism of monocyte transcriptome in individuals with chronic low-grade inflammation. - So, Jisun.; Tai, Albert K.; Lichtenstein, Alice H.; Wu, Dayong.; Lamon-Fava, Stefania. (Tufts University. Tisch Library., 2021)
Keywords: Antigen-presenting cells, Bone marrow-derived macrophages, Docosahexaenoic acid, Eicosapentaenoic acid, False discovery rate, High-sensitivity C-reactive protein, Interferon, The Immunological Genome Project, Ingenuity pathway analysis, Interferon regulatory factors, Interferon signature genes, Macrophage-specific interferon signature genes, Major histocompatibility complex, Nuclear factor kappa B, Peripheral blood mononuclear cells, Principal component analysis, Programmed cell death protein 1/programmed cell death-ligand1, Systemic lupus erythematosus, T helper type 1, TNF receptor-associated factor.; Springer Open.